Titanium Nanobowl-Based Nest-Like Nanofiber Structure Prepared at Room Temperature and Pressure Promotes Osseointegration of Beagle Implants - Sun, Lei; Chen, Xuzhuo; Mu, Haizhang; Xu, Yin; Chen, Ruiguo; Xia, Rong; Xia, Lunguo; Zhang, Shanyong (Frontiers in Bioengineering and Biotechnology, 2022)
The nest-like nanofibers structure has potential applications in surface modifications of titanium implants. In this study, nest-like nano fibers structure was prepared on titanium surface at room temperature and pressure by using nano-bowl template assisted method combined with alkali etching. The characterization and biocompatibility of this material were analyzed by cellular adhesion, death, CCK-8, ALP, and RT–PCR assays in vitro and evaluated osseointegration by micro-CT and fluorescent labeling in vivo. The results showed that this nest-like nanofibers structure has a firmer and asperate surface than nanotubes, which leads to better cellular adhesion, proliferation, and differentiation capacity. In a beagle alveolar bone implant model, the nest-like nanofibers structure showed a better osseointegration capacity. In conclusion, this nest-like nanofibers structure has potential applications in dental implantology.